2016
DOI: 10.1161/circoutcomes.115.002043
|View full text |Cite
|
Sign up to set email alerts
|

Use of Contraindicated Antiplatelet Medications in the Setting of Percutaneous Coronary Intervention

Abstract: Background Several antiplatelet medications used during and after percutaneous coronary intervention (PCI) are contraindicated for specific patient groups. A broad assessment of contraindicated medication use and associated clinical outcomes is not well described. Methods and Results Using national VA CART Program data for all PCI between 2007-2013, we evaluated patients with contraindications to commonly used antiplatelet medications during and after PCI, defined in accordance with package inserts. Adjusted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Indeed, contraindications to antithrombotic therapy are not uncommon in thrombotic disorders. A national cohort study in the U.S. showed that antithrombotic therapy was contraindicated for up to 18% of patients who underwent percutaneous coronary intervention [ 23 ]. Variability in the clinical characteristics of patients results in different bleeding risks associated with antithrombotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, contraindications to antithrombotic therapy are not uncommon in thrombotic disorders. A national cohort study in the U.S. showed that antithrombotic therapy was contraindicated for up to 18% of patients who underwent percutaneous coronary intervention [ 23 ]. Variability in the clinical characteristics of patients results in different bleeding risks associated with antithrombotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The study period of each cohort began when the most recently marketed drug of the comparison became available (July 2009 for cohort 1 and October 2011 for cohorts 2 and 3) and ended on 30 September 2015. Prasugrel is contraindicated in patients with a history of stroke and is not indicated post ACS that was treated medically or led to CABG . Accordingly, we only included patients undergoing PCI with stenting without a history of stroke (ischemic or hemorrhagic) in cohorts including prasugrel (ie, in cohorts 1 and 3).…”
Section: Methodsmentioning
confidence: 99%